Angiotensin-(1-7) attenuates damage to podocytes induced by preeclamptic serum through MAPK pathways - TIAN, JIMEI; ZHANG, LIHONG; ZHOU, YUNJIAO; XIAO, JING; LI, SHERAN; CHEN, YAPING; QIAO, ZHONGDONG; NIU, JIANYING; GU, YONG (International journal of molecular medicine, 2014)
The underlying mechanisms of proteinuria, a main characteristic of preeclampsia (PE), have not yet been fully elucidated. Evidence indicates that the renin-angiotensin system (RAS) is involved in the pathogenesis of this disease, including decreased angiotensin-(1-7) [Ang-(1-7)] levels in the circulation and urine. In the present study, we examined the damage to podocytes induced by preeclamptic serum and the effects of Ang-(1-7) on podocytes treated with preeclamptic serum, as well as the underlying mechanisms. The podocytes were incubated with serum obtained from women with PE or with serum from women with normal pregnancies for different periods of time. Cell viability was determined by CCK-8 assay. The cells were treated with various concentrations of Ang-(1-7) and A779 [an (Ang-(1-7) antagonist]. The effects of Ang-(1-7) on the expression of podocyte-specific proteins [nephrin, Wilms tumor-1 (WT-1) and podocin] and the phosphorylation of mitogen-activated protein kinases (MAPKs) were investigated by western blot analysis. Changes in F-actin rearrangement were determined by immunofluorescence. Podocyte apoptosis was determined by flow cytometry. The results revealed that in the cultured podocytes incubated with preeclamptic serum, there was a decrease in the expression of podocyte-specific proteins (nephrin and WT-1 but not podocin), a rearrangement of F-actin and apoptosis compared with the control group. However, treatment with Ang-(1-7) attenuated podocyte injury in the preeclamptic group, which may be mediated through the downregulation of MAPK (p38, ERK1/2 and JNK) phosphorylation. Thus, our data suggest that Ang-(1-7) plays a protective role in PE through the downregulation of MAPK phosphorylation.